2002
DOI: 10.1159/000066022
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Neuropathological Correlates of Apolipoprotein E Genotype in Dementia with Lewy Bodies

Abstract: Dementia with Lewy bodies (DLB) represents the second commonest cause of dementia in the elderly following Alzheimer’s disease (AD). Whilst the presence of Lewy bodies is essential, DLB shares with AD the presence of senile plaques (SP), but neurofibrillary tangles (NFT) are not a necessary feature. The apolipoprotein E (APO E) Ε4 allele is the most consistently associated genetic risk factor for AD and has also been shown to associate with DLB. We have therefore analysed the APO E Ε4 allele in a large series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 30 publications
6
33
0
Order By: Relevance
“…This fi nding is consistent with several other studies which also found no difference in the 4 allele frequency between AD and DLB [34][35][36] . In addition, the frequency of atrophic changes seen on CT scans was not different between the two groups.…”
Section: Discussionsupporting
confidence: 93%
“…This fi nding is consistent with several other studies which also found no difference in the 4 allele frequency between AD and DLB [34][35][36] . In addition, the frequency of atrophic changes seen on CT scans was not different between the two groups.…”
Section: Discussionsupporting
confidence: 93%
“…For instance, the apolipoprotein-E ε4 (APOE ε4) gene is the most consistently associated genetic risk factor for AD [69][70][71]. The APOE gene has three major isoforms -ε2, ε3 and ε4, which differ from one another only by a single amino acid residue.…”
Section: Interactions Between Buche and Other Ad Susceptibility Genesmentioning
confidence: 99%
“…Findings regarding APOE polymorphisms in DLB have so far been inconclusive. Some studies show evidence for more frequent occurrence of e4 alleles in DLB compared to normal controls but similar to AD, indicating that DLB shares the APOE 4 allele with AD as a common risk factor, although there may be some differences in the way the e4 allele affects the phenotypic expression of disease [42,43] . Others studies, however, have been unable to reproduce this finding and have shown a similar proportion of APOE 4 in DLB and controls [44] , including a recent study with pathologic confirmation of the diagnosis [20] .…”
Section: Genetic Testingmentioning
confidence: 99%